Maintaining Empathy and Relational Integrity in Digitally Mediated Social Work: Practitioner Strategies for Artificial Intelligence Integration - Chen, Yih-Chang; Lin, Chia-Ching (Buletin Ilmiah Sarjana Teknik Elektro, 2025)
This study addresses the critical challenge of preserving relational integrity in social work practice within artificial intelligence (AI)-enhanced environments. While AI technologies promise operational efficiency, their impact on empathy and human connection in social work is not fully understood. This research aims to explore how social workers maintain relational integrity when interacting with clients through AI tools, providing practical strategies and theoretical insights. The research contributes to the field by proposing a relational framework for AI integration in social work practice, emphasizing human-centered principles. The study utilizes a qualitative phenomenological approach, drawing on 24 licensed social workers from diverse sectors (e.g., child welfare, elder care, and mental health) in three urban areas known for AI adoption. Data collection involved semi-structured interviews and artifact analysis, including AI interface screenshots and decision-making protocols, to capture practitioner experiences. Findings reveal three key themes: reframing empathy in digital interactions, AI as a dual partner and adversary, and ethical tensions. Results indicate that video calls and visual aids are crucial for preserving empathy, while social workers employ proactive strategies to manage AI’s limitations. The study highlights the need for clear guidelines, interdisciplinary collaboration, and training to ensure AI supports relational practices rather than replacing them. These findings have significant policy and practice implications, offering a foundation for future research and AI tool development in social services.